2017
DOI: 10.1155/2017/6230138
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Malignancies in Systemic Sclerosis Patients: Case Reports and Review of the World Literature

Abstract: Background. The association of systemic sclerosis (SSc) and haematological cancers was reported in a large number of case reports and cohort studies, describing SSc patients with highly heterogeneous clinical pictures. Objective. We reviewed the literature to better describe SSc patients with haematological malignancies. Methods. SSc cases complicated by haematological malignancies described in the world literature were collected; other 2 cases referred to our centre were reported. Results. One hundred-thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 78 publications
0
15
0
8
Order By: Relevance
“…(165) Sporadic case reports have reported on the association between SSc and myeloid malignancies such as CML (166,167) and AML. (168) Colaci et al (169) reviewed SSc patients with HMs who were described in world literature, from 1954 to 2017. One hundred-thirty SSc subjects were identified including 28 with leukemia and 16 with myeloproliferative disorders (4 with myelofibrosis, 1 with polycythemia vera, and 11 with CML).…”
Section: Inflammatory Bowel Disease and Myeloid Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations
“…(165) Sporadic case reports have reported on the association between SSc and myeloid malignancies such as CML (166,167) and AML. (168) Colaci et al (169) reviewed SSc patients with HMs who were described in world literature, from 1954 to 2017. One hundred-thirty SSc subjects were identified including 28 with leukemia and 16 with myeloproliferative disorders (4 with myelofibrosis, 1 with polycythemia vera, and 11 with CML).…”
Section: Inflammatory Bowel Disease and Myeloid Neoplasmsmentioning
confidence: 99%
“…One hundred-thirty SSc subjects were identified including 28 with leukemia and 16 with myeloproliferative disorders (4 with myelofibrosis, 1 with polycythemia vera, and 11 with CML). Median time from SSc diagnosis to identification of myelofibrosis and CML was 15 (5-17) and 3 (0-8) years, respectively (169). Notably, majority of the leukemias and CML were diagnosed in the first years of disease, when the immunosuppressors are least likely to have exerted an iatrogenic effect.…”
Section: Inflammatory Bowel Disease and Myeloid Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colaci et al [26], who analysed a group of 130 systemic sclerosis patients with haematological cancers, demonstrated B-cell non-Hodgkin lymphoma in about 50% of them; multiple myeloma, chronic lymphocytic and myeloid leukaemia were found in a high percentage of patients. In single cases, Hodgkin disease, T-cell lymphoma, as well as myelofibrosis and polycythaemia vera, were diagnosed.…”
Section: Association Of Systemic Sclerosis With Myeloproliferative Anmentioning
confidence: 99%
“…The authors reported that haematological cancers were significantly more common in men than in women (28% of male patients); no correlation between the type of sclerosis and haemato-oncological disease was observed. Furthermore, the highest incidence of haematological cancers was found in the 6 th decade of life; in 60% of cases, the neoplastic disease was diagnosed within 5 years following the diagnosis of systemic sclerosis [26].…”
Section: Association Of Systemic Sclerosis With Myeloproliferative Anmentioning
confidence: 99%